Ground clutter model for forward scatter radar (FSR) with very high frequency (VHF) and ultra high frequency (UHF) bands in tropical region / Nor Najwa Ismail - Ismail, Nor Najwa (2018)
The lack of traditional radar system during this era is the inefficient to detect targets that occupied with radar absorbing material (RAM) coating. Forward scatter radar (FSR) was introduced to overcome the problem by operating via shadowing concept. The target is detected when it crosses the baseline of the transmitter and receiver of the sensor where it creates a Doppler signal to the transmitted electromagnetic wave. Equipped with omnidirectional antennas, FSR is able to form a fencing system that is useful for situational awareness not only for normal targets, but also for stealth targets. However, as the system utilized omnidirectional antennas, positioned on the ground as well as the lack of range resolution due to its configuration, the captured signal from desired target also collect the unwanted signal from the surrounding. This unwanted signal is one of the interference signal known as clutter. Clutter signal will cause false alarm during the operation. Subsequently, it is necessary for the user to indentify the characteristics of the clutter occurred in order to differentiate the signal between the target and the clutter signal. From the characteristics analysis, a clutter model can be developed to generate a simulated clutter signal as a reference signal during the operation.